2013
DOI: 10.1007/s00592-013-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory status score including IL-6, TNF-α, osteopontin, fractalkine, MCP-1 and adiponectin underlies whole-body insulin resistance and hyperglycemia in type 2 diabetes mellitus

Abstract: A state of subclinical systemic inflammation is characteristically present in obesity/insulin resistance and type 2 diabetes mellitus (T2DM). The aim of the study was to develop an integrated measure of the circulating cytokines involved in the subclinical systemic inflammation and evaluate its relation with whole-body insulin sensitivity and glucose metabolism in T2DM. T2DM patients (n = 17, M/F 13/4, age = 55.0 ± 1.7 years, BMI = 33.5 ± 1.5 kg/m(2), HbA(1c) = 7.7 ± 0.3%) and normal glucose-tolerant (NGT) sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(156 citation statements)
references
References 43 publications
9
129
1
12
Order By: Relevance
“…Furthermore, IL-6 regulates/stimulates production of cell adhesion molecules, chemotactic mediators, and acute phase protein, and mediates the release of other cytokines that amplify the inflammatory response (35)(36)(37). Similar to our result, other studies have shown that T2DM individuals have higher circulating IL-6 levels when compared to non-diabetic controls (38)(39)(40)(41)(42)(43). The increased levels of IL-6 and other inflammatory markers (IL-1β, CRP) emerge as early predictors of T2DM, preceding its clinical onset (44).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, IL-6 regulates/stimulates production of cell adhesion molecules, chemotactic mediators, and acute phase protein, and mediates the release of other cytokines that amplify the inflammatory response (35)(36)(37). Similar to our result, other studies have shown that T2DM individuals have higher circulating IL-6 levels when compared to non-diabetic controls (38)(39)(40)(41)(42)(43). The increased levels of IL-6 and other inflammatory markers (IL-1β, CRP) emerge as early predictors of T2DM, preceding its clinical onset (44).…”
Section: Discussionsupporting
confidence: 81%
“…A recent report assessing suitable biomarkers for evaluation of inflammation suggested that potentially patterns or clusters, as opposed to single inflammatory variables, may be more robust as biomarkers of inflammation (46) . In line with this report, a number of research groups have utilised inflammatory scores encompassing a range of inflammatory and antiinflammatory markers to assess sub-clinical inflammation and relating this to insulin sensitivity, which could be used to stratify cohorts based on inflammatory phenotype (114)(115)(116) . An increase in the inflammatory score was associated with an increase in IR, with a high inflammatory score associated with increased BMI, waist circumference and higher blood pressure (115) .…”
Section: Future Perspectives: a Personalised Nutrition Approachmentioning
confidence: 88%
“…Overall, our data placed the upregulation of α-cell mass at a stage where β-cells exhibit normal or even enhanced function, which suggests that the upregulation of α-cell mass could be a primary driving force for hyperglycemia in animal models and human type 2 diabetes patients. The underlying mechanism could be an enrichment of some cytokines and microRNAs in subjects that have obesity, insulin resistance or type 2 diabetes (Daniele et al, 2014;Guardado-Mendoza et al, 2013;Poy et al, 2009), which selectively preserve the upregulation of α-cell mass (Ellingsgaard et al, 2008;Poy et al, 2009). Consistent with this idea, most patients with glucagon-secreting pancreatic neuroendocrine tumors are diabetic (Eldor et al, 2011).…”
Section: Discussionmentioning
confidence: 99%